A Comparative Study of Destination Selection Attributes among Island Tourists - Ismail, Fathilah; Puad Mat Som, Ahmad; Alia Fahada W Ab Rahman1, Roseliza Mat Alipiah, N; Mat Alipiah, Roseliza (International Journal of Engineering and Technology, 2018)
The objective of this research is to examine differences in the choice of destination attributes, from the perspective of cross-cultural visitors and local islanders at two world-class islands in Malaysia. Using a close-ended questionnaire and random convenience sampling method, data collection has been carried out at two most visited islands in Terengganu; Redang and Perhentian. A total of 391 respondents (tourists and local hosts) was involved in this study. The outcomes of this research have demonstrated that local hosts and island travelers responded to destination selection attributes differently. The hosts were concerned with the environment and island activities, while tourist groups emphasized on the availability of services and facilities on the islands. This study also highlights that Malay and western tourist have a significant different perception with regard to destination selection attributes. Western tourist are also seeking a chance to be part of the island community and take part in their daily lifestyle. This research provides information on destination selection attributes and highlights the importance of understanding about cultural differences among tourists and local hosts in delivering satisfactory services for the survival of island tourism over the long term.Â Â